Acute appendicitis in children: How is it different than in adults? - Dahal, Geha Raj (Grande Medical Journal, 2019)
Acute appendicitis is common in both children and adults. As children are different than adults in many aspects, the disease process, presentation, and outcome are different. Children have more complicated appendicitis. This article discusses the differences of acute appendicitis in children.